EVALUASI SISTEM INFORMASI MANAJEMEN KEPEGAWAIAN BERDASARKAN METODE PIECES DI PUSKESMAS WILAYAH KERJA DINAS KESEHATAN KABUPATEN CILACAP TAHUN 2014 - Eka Apriyanti; Siti Nurhayati; Setyowati Rahardjo (Kesmas Indonesia, 2015)
Information system evaluation necessary to improve the quality or make changes according to the needs of the organization. A method of pieces is a framework for the evaluation of information system that evaluates the performance , information, the economic aspect, security aspects, the aspect of efficiency and the aspect of service. The purpose of research know evaluation based on appearance, information, the economic aspect, security aspects, the aspect of efficiency and the services the type of research is research descriptive evaluative with the approach of cross sectional with a method of quantitative research. As many as 71,4% of respondents felt aspect entered in the performance category either. As many as 60,7 % of respondents felt aspects information data SIMKA entrance on good category. As many as 53,6% of respondents felt the aspect of the economic aspect SIMKA enters at the entrance on the category of no good. As many as 53,6% of respondents felt aspect control/security SIMKA already good. As many as 57,1% of respondents felt efficiency aspects on SIMKA already good. As many as 57,1% of respondents felt aspects on SIMKA service entrance on the category of no good. The need to give additional knowledge related to officials SIMKA. The official and the Puskesmas have to increase the budget allocation for special treatment SIMKA good for software, hardware and facilities SIMKA. The official need to cooperate with third parties in this developer/vendor for developing applications software to improve sensitivity against mistakes and good at input/ouput data or information and adder a manual on aid-application to know and correct the mistakes happen.